Quality Assessment of Commercial Fruit Juices and Health Hazards in Slemani City- Kurdistan Region/ Iraq - Kawa Khwarahm Hamafarj 1, Kadamkheer Tawfiq Aziz 2, Attallah Omar Qasem3, Halgord Ali M. Farag4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Fruit juices are especially valued in the human diet as these contain micronutrients, fiber, potassium, vitamin C, which work as antioxidants within the body as well as bio-functional components. The goal of this study is to determine the levels of Iron Fe, Zinc Zn, Magnesium Mg, Sodium Na, Potassium K, Calcium Ca and heavy metal manganese Mn, mercury Hg, Lead Pb as fruit juice consumed largely and will be in raise daily. Sixty-nine samples of different fruit juice were bought from retail markets in Sulaimani city, were analyzed using wet methods. The results obtained showed the ranges of the metals detected in all the of fruit juice were; Iron Fe (0-2), Zinc Zn (0 ), Manganese Mn (0), magnesium Mg (0-0.6), Sodium Na (0-22.9), Potassium K (0-19.2), Calcium Ca (0-29) and heavy metal mercury Hg (0-0.25), Lead Pb (0-4) mg/L. The mean value of Iron Fe, Magnesium Mg, Sodium Na, Potassium K, Calcium Ca and heavy metal mercury Hg, Lead Pb 0.421 , 0.16 , 4.188 , 3.348 , 7.362 ,0.029 , 0.578mg/L) respectively, Zinc and Manganese were not detected in any samples,some of the samples have nutrient value for sodium, potassium and calcium.